Temps du care et organisation sociale du travail en famille - Aurélie Damamme; Patricia Paperman (Temporalités)
The organization of Care in families challenges the ways the work accomplished by a wide range of agents and their various temporalities are accounted for. If gender and a quasi-permanent temporal availability allow one to combine Care and household work, it is the task of coordination in the long term that specifies Care, both as labour and ethics. Creating coherence between protagonists - professionals and non professionals, family members and quasi-relatives - challenges the separation between private and public spheres. As a process integrating different temporalities, Care is described as both an organization in itself and a sequence of phases. Maintaining continuity and coherence is identified as the main role and concern of the principal caregiver. Acknowledging the political importance of time in the production of Care jeopardizes the different hierarchies involved according to gender, social class and race.